Reduced vascular smooth muscle BK channel current underlies heart failure‐induced vasoconstriction in mice. Issue 5 (16th January 2013) - Wan, Elaine; Kushner, Jared S.; Zakharov, Sergey; Nui, Xiao‐wei; Chudasama, Neelesh; Kelly, Christopher; Waase, Marc; Doshi, Darshan; Liu, Guoxia; Iwata, Shinichi; Shiomi, Takayuki; Katchman, Alexander; et al.
Abstract : Excessively increased peripheral vasoconstriction is a hallmark of heart failure (HF). Here, we show that in mice with systolic HF post–myocardial infarction, the myogenic tone of third‐order mesenteric resistance vessels is increased, the vascular smooth muscle (VSM) membrane potential is depolarized by ~20 mV, and vessel wall intracellular [Ca 2+ ] is elevated relative to that in sham‐operated control mice. Despite the increased [Ca 2+ ], the frequency and amplitude of spontaneous transient outward currents (STOCs), mediated by large conductance, Ca 2+ ‐activated BK channels, were reduced by nearly 80% ( P <0.01) and 25% ( P <0.05), respectively, in HF. The expression of the BK α and β1 subunits was reduced in HF mice compared to controls (65 and 82% lower, respectively, P <0.01). Consistent with the importance of a reduction in BK channel expression and function in mediating the HF‐induced increase in myogenic tone are two further findings: a blunting of paxilline‐induced increase in myogenic tone in HF mice compared to controls (0.9 vs. 10.9%, respectively), and that HF does not alter the increased myogenic tone of BK β1‐null mice. These findings identify electrical dysregulation within VSM, specifically the reduction of BK currents, as a key molecular mechanism sensitizing resistance vessels to pressure‐induced vasoconstriction in systolic HF.—Wan, E., Kushner, J. S., Zakharov, S., Nui, X‐W., Chudasama, N., Kelly, C., Waase, M., Doshi, D., Liu, G., Iwata, S., Shiomi, T., Katchman, A., D'Armiento, J., Homma, S., Marx, S. O. Reduced vascular smooth muscle BK channel current underlies heart failure‐induced vasoconstriction in mice. FASEB J. 27, 1859–1867 (2013). www.fasebj.org